View of an evaluation framework for legal entity state universities in indonesia: integration and measuring institusional effectiveness - Rosmiati, Rosmiati; Iwan Putra; Dwijayanti, Novia Sri; Sari, Nurmala; Nasori, Ahmad (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This research is motivated by the turbulent development of economic improvement in the world of education regarding Legal Entity State Universities in Indonesia, which integration measuring institutional effectivenes, and evaluation framework which are needed in the tertiary environment. Therefore, it is necessary to design concepts, models of good practice, and implementation in Legal Entity State Universities in Indonesia. The method used is a qualitative method using text-based analysis, which is called textual analysis of various reports, official documents, guidelines, and procedures. This research aims to examine and analyze how legal entity state universities influence the integration of institutional effectiveness and Institutional theory-based research as a form of assessment of existing models and regulations. The results showed that the shift in the institutional form of Legal Entity State Universities (PTNBH) has brought about changes in strategic leadership models such as in private organizational governance. The analysis result found that dominant evaluation framework model legal entity state universities is the main idea, the main model in providing recommendations for good management development and preparation for handling problems with legal entity state universities in Indonesia which have not yet been implemented Researchers in this field and in Indonesia in general. The findings show that the evaluation framework model in legal entity state universities still have several problems including concept (4 findings), model (3 findings), process audit (2 finding), and implementation (1 findings). So it is necessary to immediately carry out harmonization and explain the formulation of several